A review on enabling technologies for high power density power electronic applications. (2021) - Mahesh, M.; Vinoth Kumar, K.; Abebe, Mesfin; Udayakumar, L.; Mathankumar, M.
Abstract: Power Electronic Systems for various applications have gone through several stages of development during last five decades. Its development especially in high power density has been significantly accelerated from late 1980's. In addition to the high-power density of converters, efficiency, cost, operating temperature of converters have also become important key factors in miniaturization of power converters. This paper presents the contributions in the recent years in high power density converter technologies, which show these technologies have envisaged in miniaturization of power sources for various applications. Diversified advanced technologies inclined in achieving high power density of converters are described along with their layouts and structures which are based on the materials used. A glimpse into the future based on the current advanced technological trend is offered.